Evaluation of the effect of rainfall on COVID-19 transmission in Terengganu, Malaysia - Mohamed Nawi, Nur Fatin Auni; Che Dom, Nazri; Dapari, Rahmat; Salim, Hasber; Precha, Nopadol (Universiti Malaysia Terengganu, 2022)
One of the variables leading to the global spread of COVID-19 cases is the weather, which includes temperature and air quality. In this study, an investigation of the association between precipitation and COVID-19 cases was conducted to provide useful information on the possibility of this climate factor (precipitation) on the progression of COVID-19 cases for an appropriate management strategy. Secondary COVID-19 and rainfall data obtained from the Ministry of Health and the Meteorological Department in Malaysia were used for the study. The collected data were subjected to Pearson correlation analysis. The results of this study showed that both rainy days and rainfall amount were insignificant to COVID-19 cases, indicating that rainfall amount was not associated with COVID-19 transmission in Terengganu, Malaysia. Thus, this discovery could be used to inform individual and COVID-19 supervisors and the government as it prepares for the new weather season.